The Lapidary's Nosegay. - Candland, Lara (Mountain west poetry series., 2018)
"The Lapidary's Nosegay, Lara Candland's primer of poems, presents to readers a bouquet of resplendent poems that Candland has created, collaged, curated, and re-imagined by using the rich floral and gem imagery in the poetry of Emily Dickinson as her primary source material. Dickinson and Candland share linguistic and theological roots in the Bible, nineteenth-century American Protestantism, and a lexicon distinctive to their specific individuarian communities, and this collection of poems draws a serpentine kind of map across nearly two centuries, journeying from Amherst, Massachusetts to Provo, Utah, from Dickinson's severe and lush New England to Candland's own jagged, harsh, and stunning high desert Utah. The Lapidary's Nosegay explores the ways that both poets have simultaneously challenged and embraced the axiomatic constraints of religion, landscape, and cultural conventions and expectations of each poet's time and place. Aesthetically, Candland attempts to challenge the hierarchies of the page through linguistic, typographic, and sonic experimentation. The Lapidary's Nosegay carries Dickinsonian echoes to alliterative and parenthetic excessivities that indicate sound stresses, or that pictographically invoke sun, god, ghosts, ecstasy, and the jewels and flowers tumbling throughout Dickinson's own poems. This collection works at toppling textual hierarchies, systematically jumbling sound, text, meaning, symbol, and context, entering the vein of radical American aesthetics, politics, and culture that have shaped Candland's life and poetics."--Provided by publisher.